Board Diversity And Risk-Taking: Empirical Evidence Of Indonesian Banking Industry - Darus Altin; Ridwan Nurazi; Fitri Santi; Syaiful Syaiful (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
Goals of this research to prove influence board_diversity on the risk-taking behaviour of Indonesian banks. Sample is used 53 bank commercial with periode from 2000-2018. We find effect positive from board diversity on risk taking commercial bank in Indonesia. Size of the diversified role of the board of directors significant effect on risk. Our study provides significant findings with respect to the development of risk-taking model behavior of Indonesian banks.Keywords: